Association between gene polymorphism and adverse effects in cancer patients receiving docetaxel treatment: a meta-analysis - Yan, Mingrui; Fan, Xiaoyu; Si, Hongyanhua; Wang, Xiaoyu; Wang, Zhe; Wang, Zhen; Lv, Xin; Yin, Hang; Jia, Yanyan; Jiang, Lili; Xia, Yangliu; Liu, Yong (Cancer chemotherapy and pharmacology, 2022)
Purpose Large interindividual variability in the pharmacokinetic properties of docetaxel has been reported, with the clearance of docetaxel varying nearly six fold, in which pharmacogenetics of docetaxel may play an essential role in addition to physiological factors. The association between the gene polymorphism and risk of adverse clinical effects in docetaxel treated patients has been examined in several studies, but their conclusions are, to some extent, controversial. To clarify the role of gene polymorphism in the clinical outcomes of docetaxel treatment, a meta-analysis was performed in the present study. Methods Pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were employed to evaluate the impact of gene polymorphisms of CYP3A4, CYP3A5 and ABCB1. Four studies with 485 subjects were included in this study. Fixed or random-effects model was chosen according to heterogeneity to conduct the meta-analysis. Publication bias was evaluated by fail-safe numbers. Results Significant association was identified between the ABCB1 C3435T (rs1045642) polymorphism and risk of short-term recurrent hematological toxicity (TT vs. CC + TC OR = 2.91, 95% CI 1.30–6.52, P = 0.009; TT vs. CC OR = 4.23, 95% CI 1.69–10.57 P = 0.002). The association of the ABCB1 G2677T/A (rs2032582) polymorphism with risk of fluid retention was statistically significant (T(A)/T(A) vs. GG + GT(A) OR = 2.08, 95% CI 1.16–3.73, P = 0.01). No statistically significant association between the CYP3A5 A6986G (rs776746) polymorphism and adverse effects was observed in this study. Due to the limitations of included literature, we did not conduct meta-analysis on CYP3A4 gene polymorphism and adverse effects. Conclusion An association between the ABCB1 C3435T (rs1045642), ABCB1 G2677T/A (rs2032582) polymorphism and risk of adverse effects of docetaxel was found by our meta-analysis. Namely, the TT homozygotes of the ABCB1 C3435T polymorphism may be associated with the risk of hematological toxicity. ABCB1 G2677T T(A)/T(A) genotype may be associated with the fluid retention. Trail registration PROSPERO 2020 CRD42020203132.